Pengembangan Bahan Ajar Ilmu Pengetahuan Alam (IPA) Berbasis Problem Based Learning (PBL) - M. Nasri; Marhamah Marhamah; Hartini Haritani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
This research is motivated by a needs analysis of consistent teaching materials. This study aims to develop a natural science teaching material product based on Problem Based Learning (PBL), as well as to test its effectiveness through a one group sample pretest and posttest design. The data validation results by three experts include: material experts, linguists, and technology experts, as well as user responses, getting a comprehensive average score of 3.40, with an ideal standard score of 4.0. While the empirical test data through one group sample pretest and posttest design on 51 test samples, obtained an N-Gain value with an average score of 0.45 with a (medium) category. Thus, it is recommended that Problem Based Learning (PBL) natural sciences teaching materials are very feasible and effective to be used in learning activities in Elementary Schools and Islamic Elementary Schools.